Validation of Liquid Chromatography Coupled with Tandem Mass Spectrometry for the Determination of 12 Tyrosine Kinase Inhibitors (TKIs) and Their Application to Therapeutic Drug Monitoring in Adult and Pediatric Populations - Marie Bellouard; Jean Donadieu; Pauline Thiebot; Etienne Giroux Leprieur; Philippe Saiag; Isabelle Etting; Pamela Dugues; Emuri Abe; Jean-Claude Alvarez; Islam-Amine Larabi (MDPI AG, 2023)
Tyrosine kinase inhibitors (TKIs) are used as targeted cancer therapies in adults and have an off-label pediatric application for the treatment of Langerhans cell histiocytosis. A multitarget LC-MS/MS method was developed and validated for the determination of alectinib, alectinib-M4, binimetinib, cobimetinib, crizotinib, dabrafenib, encorafenib, imatinib, lorlatinib, osimertinib, AZ5104, and trametinib. A total of 150 µL of internal standard methanolic solution was added to 50 µL of plasma sample to precipitate proteins. After centrifugation, 10 µL of the supernatant was injected into the chromatographic system. The chromatographic separation was conducted on a Kinetex C18 Polar column with a gradient of 2 mM ammonium formate in 0.1% formic acid and acetonitrile over 5 min. Limits of detection and quantification, linearity, accuracy, precision, selectivity, carryover, matrix effect, recovery, and stability were evaluated and satisfied EMA guidelines on bioanalytical methods. This method has been successfully applied to the therapeutic drug monitoring (TDM) of adults with melanoma and lung cancer, as well as children with histiocytosis, to improve the pharmacokinetic data for these drugs, with the aim of enhancing the therapeutic management and follow-up of patients. Blood concentrations of trametinib and binimetinib were different in the two groups, highlighting the age-related inter-individual variability of these molecules and the need for TDM.